The Effect of Workload and Work Environment on Medication Error through Adherence to Medication Procedures in Hospitals: A Literature Review - Sri Fatmiyati; Burhanuddin Ichsan; Muzakar Isa (Universitas Muhammadiyah Surakarta, 2025)
This article aims to develop a proposition about the factors that influence medication errors in hospitals. This study selected articles using the keyword